Debris Cloud Material Characterization for Hypervelocity Impacts of Single- and Multimaterial Projectiles on Thin Target Plates - William P. Schonberg (Shock and Vibration)
The key to conducting an accurate damage assessment of a target impacted by a high speed projectile is the use of a robust assessment methodology. To accurately determine total target damage, a damage assessment methodology must include the effects of discrete impacts by solid debris cloud fragments as well as impulsive loadings due to molten and vaporous debris cloud material. As a result, the amount of debris cloud material in each of the three states of matter must be known to accurately assess total target damage and break-up due to a high speed impact. This article presents a first-principles based method to calculate: the amount of material in a debris cloud created by a perforating hypervelocity impact that is solid, molten, and vaporous; the debris cloud leading edge, trailing edge, center-of-mass, and expansion velocities; and the angular spread of the debris cloud material. The predictions of this methodology are compared against those of empirically based lethality assessment schemes as well as numerical and empirical results obtained in previous studies of debris cloud formation.